Immunoscintigraphy with Anti-225.28S for Ocular Melanoma - a Comparison with Histology and Immunohistochemistry, - Bräutigam, P.; Loeffler, Karin U.; Krause, T.; Högerle, S.; Simon, J.; Moser, E. (Nuklearmedizin - NuclearMedicine, 1997)
Aim: The purpose of this prospective study was to evaluate the value of Immunoscintigraphy (ISG) with anti-225.28S in clinically suspected ocular melanoma. Methods: For this purpose standardized ISG was performed in 36 patients using both planar acquisition and emission computed tomography (ECT). Ocular melanoma was present in 31 patients. In 21 patients therapy was enucleation of the eye. These specimens were evaluated by histology and immunohistochemistry in 11 of 21 patients. Results: Regarding the clinical diagnosis, ISG was positive only in 15 of 31 patients with ocular melanoma, regarding histology in 11 of 21 and regarding immunohistochemistry in 5 of 6 patients with a positive Immunoreaction. 5 patients showed no immunoreactivity, their ISG was negative. Conclusion: Thus a good correlation between ISG and immunohistochemistry was observed. However ISG using the cutaneous melanoma antibody 225.28S cannot be recommanded for the diagnostic work-up of an ocular melanoma considering the poor immunoreactivity.
Keywords: Immunoscintigraphy; ocular melanoma; immunohistochemistry; antibody 225.28S